2012
DOI: 10.1007/s10493-012-9570-9
|View full text |Cite
|
Sign up to set email alerts
|

Ticks (Acari: Ixodidae) associated with small terrestrial mammals in the state of Minas Gerais, southeastern Brazil

Abstract: From June 2005 to November 2010, 43 small mammals encompassing 6 species of Didelphimorphia, 8 species of Rodentia, and 1 species of Lagomorpha were found parasitized by ticks in the state of Minas Gerais, southeastern Brazil. Nine tick species, in total 186 specimens, were identified as follows: Amblyomma cajennense (larvae and nymphs) on opossums and rodents; Amblyomma ovale (nymphs) on rodents; Amblyomma parvum (nymphs) on rodents; Amblyomma coelebs (nymphs) on opossums; Amblyomma dubitatum (nymph) on oposs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 25 publications
3
27
1
18
Order By: Relevance
“…Previous studies indicated that immature A. ovale parasitize mainly rodents of the family Cricetidae (SZABÓ et al, 2013;SPoNCHIADo et al, 2015) and echimyidae (SARAIVA et al, 2012), whereas the adult stage parasitizes chiefly wild carnivores and domestic dogs (GUGLIeLMoNe et al, 2003). In this study, immature A. ovale were reported on four species of rodents, which includes the first records for O. flavescens, O. nigripes and S. agouya.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous studies indicated that immature A. ovale parasitize mainly rodents of the family Cricetidae (SZABÓ et al, 2013;SPoNCHIADo et al, 2015) and echimyidae (SARAIVA et al, 2012), whereas the adult stage parasitizes chiefly wild carnivores and domestic dogs (GUGLIeLMoNe et al, 2003). In this study, immature A. ovale were reported on four species of rodents, which includes the first records for O. flavescens, O. nigripes and S. agouya.…”
Section: Discussionsupporting
confidence: 54%
“…Although A. sculptum (formerly known as Amblyomma cajennense) is widely distributed in southeastern Brazil (NAVA et al, 2014), this tick species has a preference for medium to largesized mammals (BARRoS-BATTeSTI et al, 2006) and is rarely found on Cricetidae rodents, such as Cerradomys subflavus and O. nigripes in Minas ----------------------Number of infested animals / Number of examined animals (Prevalence); Mean intensity * -- Gerais (SARAIVA et al, 2012) and Calomys callosus and Rhipidomys macrurus in Mato Grosso do Sul (SPoNCHIADo et al, 2015). The present reports of I. schulzei on two species of Oligoryzomys are unprecedented for this tick.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amblyomma coelebs Neumann, 1899 is established in the Neotropical and Nearctic regions MARTINS et al, 2011;MARTINS et al, 2014a;SPONCHIADO et al, 2015;WITTER et al, 2016), Didelphimorphia (LABRUNA et al, 2005a;SARAIVA et al, 2012;SPONCHIADO et al, 2015;WITTER et al, 2016), Cingulata (MARTINS et al, 2014a), Artiodactyla (LABRUNA et al, 2005a, Carnivora (LABRUNA et al, 2002a;2005b;MARTINS et al, 2011;WITTER et al, 2016) and on humans (LABRUNA et al, 2005a;GARCIA et al, 2015). Although few records of immature A.…”
Section: Amblyomma Brasiliense Aragão 1908 Occurs Inmentioning
confidence: 99%
“…With respect to host range, adult A. parvum commonly parasitizes a variety of medium to large-sized domestic and wild animals, including humans (Jones et al, 1972;Guglielmone et al, 1991;Nava et al, 2006;2008b), while the immature stages are commonly collected from rodents, in particular members of the Caviidae and Echimyidae families (Labruna et al, 2005;Nava, 2006;2008b;Saraiva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%